KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PESERTA DIDIK JOGJA FLIGHT EDUCATION CENTER BALIKPAPAN - Abdiannur Abdiannur (Jurnal GeoEkonomi, 2021)
This study aims to determine the effect of simultaneously or partially the variables of physical evidence, empathy, responsiveness, reliability, and assurance on student satisfaction at Jogja Flight Education Center Balikpapan. The population in this study were students who were registered in 2015-2019, amounting to 210 students. By using random sampling technique so that it can be determined the number of samples in this study amounted to 63 students. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 25. The results of this study indicate that simultaneously the variables of physical evidence, empathy, responsiveness, reliability, and assurance have a positive and significant effect on student satisfaction on Jogja Flight. Education Center Balikpapan. While partially it can be concluded that of the five variables, the responsiveness variable has a dominant effect on student satisfaction at Jogja Flight Education Center Balikpapan.